Advance in microRNA as a potential biomarker for early detection of pancreatic cancer. Issue 1 (December 2016) - Huang, Jing; Liu, Jianzhou; Chen-Xiao, Kevin; Zhang, Xuemei; Lee, W.; Go, Vay; Xiao, Gary
Abstract Pancreatic cancer is characterized as a disease with low survival and high mortality because of no effective diagnostic and therapeutic strategies available in clinic. Conventional clinical diagnostic methods including serum markers and radiological imaging (CT, MRI, EUS, etc.) often fail to detect precancerous or early stage lesions. Development of effective biomarkers is unmet for reduction of mortality of pancreatic cancer. MicroRNAs (miRNAs) are a group of small non-protein-coding RNAs playing roles in regulation of cell physiology including tumorigenesis, apoptotic escape, proliferation, invasion, epithelial-mesenchymal transition (EMT), metastasis and chemoresistance. Various altered signaling pathways involving in molecular pathogenesis of pancreatic cancer are mediated by miRNAs as a role of either oncogenes or tumor suppressors. Among biomarkers developed including protein, metabolites, DNA, RNA, epigenetic mutation, miRNAs are superior because of its unique chemical property. Recent study suggests that miRNAs may be promising biomarkers used for early detection of pancreatic cancer. This review will update the progression made in early detection of pancreatic cancer.